Structure insight into the interfacial effect of fiber-low density polyethylene composites by the combination of experiment and finite element simulation. (July 2022) - Bai, Longshan; Cao, Changlin; Xiao, Liren; Cheng, Huibin; Liu, Zhen; Sun, Xiaoli; Xiao, Qiao; Yang, Songwei; Lin, Guoliang; Qian, Qingrong; Chen, Qinghua
Abstract: Good interfacial adhesion is one of the key factors to ensure the excellent performance of composite materials. However, the interfacial effect of fiber-polymer composites remain incompletely understood. Herein, a self-designed mold was used to prepare UHMWPE (Ultra-high molecular weight polyethylene)-fiber/LDPE (Low density polyethylene)-matrix (LU) and PET (polyethylene terephthalate)-fiber/LDPE-matrix composite materials (LP). The interfacial bonding effect was explored by the interfacial shear strength (IFSS), and the interfacial structure and failure mechanism during the fiber pull-out process were analyzed by the combination of experiment and finite element simulation. The results show that the IFSS of LU (3.59 MPa) is 3 times greater than that of LP (1.18 MPa), giving rise to a higher tensile strength. Moreover, Raman mapping and DSC results suggest that UHMWPE-fiber act as nucleation sites to improve the orientation and crystallization of LDPE molecular chains, generating an obvious interfacial transition zone between UHMWPE-fiber and LDPE, while no obvious interfacial transition zone is found between PET-fiber and LDPE. These findings will be expected to give some guidelines for the design and manufacturing high-performance fiber-polymer composites. Highlights: Interfacial shear strength is contributed to the combination of friction and bonding. There is an obvious interfacial transition zone between UHMWPE-fibers and LDPE. The UHMWPE-fibers act as nucleation sites to improve thecrystallization of LDPE.